2018
DOI: 10.1016/j.celrep.2018.11.104
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem and Progenitor Cells Are a Distinct HIV Reservoir that Contributes to Persistent Viremia in Suppressed Patients

Abstract: Highlights d Hematopoietic stem and progenitor cells can serve as longterm reservoirs of HIV d HSPCs harbor both infectious and defective proviral genomes d HSPCs are an important source of residual plasma virus in treated people d Clonally amplified HIV proviruses contribute to residual plasma virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 51 publications
(66 reference statements)
1
31
0
1
Order By: Relevance
“…Viral DNA has also been detected in hematopoietic stem cells (HSCs) from ART-treated patients, which could demonstrate their involvement in HIV-1 persistence (Sebastian et al, 2017;Zaikos et al, 2018). Despite the limited infection and detection of HSCs in a subset of patients (McNamara et al, 2013), their role as a viral reservoir may be crucial.…”
Section: Non-t Cell Reservoirsmentioning
confidence: 99%
“…Viral DNA has also been detected in hematopoietic stem cells (HSCs) from ART-treated patients, which could demonstrate their involvement in HIV-1 persistence (Sebastian et al, 2017;Zaikos et al, 2018). Despite the limited infection and detection of HSCs in a subset of patients (McNamara et al, 2013), their role as a viral reservoir may be crucial.…”
Section: Non-t Cell Reservoirsmentioning
confidence: 99%
“…While it remains unclear whether infected HSPCs contribute to residual viremia after ART Mcnamara and Collins, 2011), a recent article reported that HSPCs in suppressed patients harbor functional HIV proviral genomes that often match residual peripheral viral RNA (Zaikos et al, 2018). If these findings are confirmed, HSPCs might be finally regarded as long-term viral reservoirs, because they are long-lived cells with regulated susceptibility to apoptosis (Durdik et al, 2017).…”
Section: Hspcs As Viral Reservoirsmentioning
confidence: 99%
“…HSPCs express CD4 at low levels, are capable of being infected with both X4 and R5-tropic HIV in vitro, and proviral sequences have been identified in HSPCs from patients [11,12,16,22]. Identical proviral sequences, including the same insertion site in the patient genome, were found in multiple compartments of the hematopoietic lineage including HSPCs, PBMCs (peripheral blood mononuclear cells), and BMMCs (bone marrow mononuclear cells).…”
Section: Hematopoietic Potentialmentioning
confidence: 99%
“…Identical proviral sequences, including the same insertion site in the patient genome, were found in multiple compartments of the hematopoietic lineage including HSPCs, PBMCs (peripheral blood mononuclear cells), and BMMCs (bone marrow mononuclear cells). A subset of these clonal sequences was matched to expressed cell-free virus [11]. Some cells with clonal proviral sequences matching provirus from HSPCs were not CD4+.…”
Section: Hematopoietic Potentialmentioning
confidence: 99%
See 1 more Smart Citation